Non-Evidence-Based Dietary Restrictions in Hospital Nutrition and Their Impact on Malnutrition: A Narrative Review of International and National Guidelines - Sara Carnevale; Assunta Vitale; Monica Razzi; Claudia Onori; Gianna Cornacchia; Ornella Grispo; Elena Corsinovi; Laura Rossl; Elena Spinetti; Martina Tosi; Fabrizia Lisso; Gianna Marchi (Dietetics)
Background: Malnutrition is a major issue in hospitals, impacting over 25% of patients. It can arise from a range of factors, such as chronic underfeeding, diseases, aging, and inappropriate nutritional care. Unnecessary fasting and the use of incorrect dietary prescriptions can also contribute to malnutrition, regardless of a patient’s underlying health conditions. Methods: A search strategy was applied to identify pertinent articles on the prescription and management of therapeutic diets in hospital settings from the last 10 years (2014–2024) using the PubMed database. The following English terms and their combinations were used: hospital diet, non-evidence-based dietary restriction, hospital food service, and therapeutic diets. Only national or international guidelines published in English were considered. Results: The narrative review was developed through the analysis of two guidelines on the prescription and management of therapeutic diets in hospital settings. The main non-evidence-based therapeutic diets that should have limited prescriptions are low-calorie, low-carbohydrate, low-protein, and low-sodium diets because they inevitably lead to a reduction in caloric and/or protein content, limit menu choices, and make recipes less palatable. The preventive total elimination of lactose without diagnostic confirmation should be avoided in the prescription of hospital therapeutic diets for lactose intolerance without symptoms and confirmation of diagnosis. Fasting after surgery should be avoided. The two guidelines differ in part in terminology and the bromatological composition of the diet. Conclusions: The heterogeneity of terminologies and bromatological composition leads to further confusion in determining the correct procedure for managing and prescribing therapeutic diets. Deepening and increasing research in the field of management and prescription of therapeutic diets is necessary to overcome the problem of hospital malnutrition, as the food provided through hospital food service is a very effective medicine for providing calories, macronutrients, and micronutrients.